Determinants and effects of adopting improved potato varieties in Malawi - Tsuanyo, F.F.; Otieno, D.J.; Rajendran, S.; Kapalasa, E.; Mwenye, O.; Demo, P.; Parker, M. (Elsevier, 2024)
It is crucial to comprehend the effects of adopting improved potato varieties on farmers’ welfare in Sub-Saharan Africa, especially given the growing demand for food arising from rapid urbanization. This study examines the adoption of improved potato varieties in Malawi and its effects on farmer outcomes, overall welfare and poverty. Data from a multistage sample of 277 smallholder potato growers were analyzed using the probit, endogenous switching regression and economic surplus models. Results showed that years of formal schooling, distance to closest input source, access to credit, number of adopters known by the farmer, confidence in the extension worker’s skills and group membership positively affected the adoption of improved potato varieties. In contrast, the perceived soil fertility level negatively influenced the adoption of the improved varieties. Additionally, results revealed a significant relationship between adoption and yield and a significant negative relationship between adoption and cost of production. Similarly, adopting improved varieties leads to a total surplus between US$ 108 million to US$ 178.7 million. Furthermore, adopting improved varieties could lead to a poverty reduction of 1.61% to 2.7%. The adoption of improved varieties also decreases poverty and boosts overall economic surplus. The study recommends enhanced availability of the improved potato varieties to the public through a decentralized seed production system, seed quality monitoring and traceability. Furthermore, strengthening extension workers’ skills and farmer-to-farmer extension approaches, cooperatives, provision of microcredit, and the promotion of crop rotation and use of organic fertilizers can be implemented to facilitate potato varieties adoption and increase farmers’ yield while reducing their production costs.